A Dual-Pathogen Mitral Valve Endocarditis Caused by Coxiella burnetii and Streptococcus gordonii—Which Came First? - Kaemmerer, Ann-Sophie; Ciotola, Francesco; Geißdörfer, Walter; Harig, Frank; Mattner, Jochen; Seitz, Tatjana; Suleiman, Mathieu; Weyand, Michael; Heim, Christian (Pathogens, 2023)
Infective endocarditis (IE) is still a life-threatening disease with high morbidity and mortality. While usually caused by a single bacterium, poly-microbial infective endocarditis (IE) is rare. Here, we report a (blood-culture-negative) dual pathogen mitral valve IE caused by Coxiella burnetii and Streptococcus gordonii: A 53-year-old woman was presented to an internal medicine department with abdominal pain for further evaluation. Within the diagnostic work up, transthoracic echocardiography (TTE) revealed an irregularly shaped echogenic mass (5 × 13 mm) adherent to the edge of the posterior mitral valve leaflet and protruding into the left atrium. As infected endocarditis was suspected, blood cultures were initially obtained, but they remained negative. Chronic Q fever infection was diagnosed using serologic testing. After the occurrence of cerebral thromboembolic events, the patient was admitted for mitral valve surgery. Intraoperatively, a massively destructed mitral valve with adhering vegetations was noted. Examination of the mitral valve by broad-range bacterial polymerase chain reaction (PCR) and amplicon sequencing confirmed Coxiella burnetii infection and yielded Streptococcus gordonii as the second pathogen. Based on the detailed diagnosis, appropriate antibiotic therapy of both pathogens was initiated, and the patient could be discharged uneventfully on the 11th postoperative day after a successful minimal-invasive mitral valve replacement.
CRIS-Team Scopus Importer:2023-10-20
Keywords: blood-culture-negative endocarditis; Coxiella burnetii; dual-pathogen endocarditis; endocarditis; minimally invasive mitral valve replacement; polymicrobial infective endocarditis; Q fever; Streptococcus gordonii

High frequency of Tropheryma whipplei in culture-negative endocarditis - Geißdörfer, Walter; Moos, Verena; Moter, Annette; Loddenkemper, Christoph; Jansen, Andreas; Tandler, Rene; Morguet, Andreas J.; Fenollar, Florence; Raoult, Didier; Bogdan, Christian; Schneider, Thomas (Journal of Clinical Microbiology, 2012)
"Classical" Whipple's disease (cWD) is caused by Tropheryma whipplei and is characterized by arthropathy, weight loss, and diarrhea. T. whipplei infectious endocarditis (TWIE) is rarely reported, either in the context of cWD or as isolated TWIE without signs of systemic infection. The frequency of TWIE is unknown, and systematic studies are lacking. Here, we performed an observational cohort study on the incidence of T. whipplei infection in explanted heart valves in two German university centers. Cardiac valves from 1,135 patients were analyzed for bacterial infection using conventional culture techniques, PCR amplification of the bacterial 16S rRNA gene, and subsequent sequencing. T. whipplei-positive heart valves were confirmed by specific PCR, fluorescence in situ hybridization, immunohistochemistry, histological examination, and culture for T. whipplei. Bacterial endocarditis was diagnosed in 255 patients, with streptococci, staphylococci, and enterococci being the main pathogens. T. whipplei was the fourth most frequent pathogen, found in 16 (6.3%) cases, and clearly outnumbered Bartonella quintana, Coxiella burnetii, and members of the HACEK group (Haemophilus species, Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae). In this cohort, T. whipplei was the most commonly found pathogen associated with culture-negative infective endocarditis. Copyright © 2012, American Society for Microbiology. All Rights Reserved.
CRIS-Team Scopus Importer:2024-02-26

Meningitis and intracranial abscess due to Mycoplasma pneumoniae in a B cell-depleted patient with multiple sclerosis - Madžar, Dominik; Nickel, Florian; Rothhammer, Veit; Gölitz, Philipp; Geißdörfer, Walter; Dumke, Roger; Lang, Roland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Mycoplasma pneumoniae, a frequent respiratory pathogen, can cause neurological disease manifestations. We here present a case of M. pneumoniae as cause of meningitis and occurrence of an intracranial abscess as a complication of mastoiditis with septic cerebral venous sinus thrombosis in a patient with multiple sclerosis on anti-CD20 therapy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Abscess; Anti-CD20 antibody; Complication; Mastoiditis; Multiple sclerosis; Mycoplasma pneumoniae; Ocrelizumab; Rituximab; Septic cerebral venous sinus thrombosis

Microbiologic diagnostics and pathogen spectrum in infective endocarditis of surgically treated patients: a five-year, retrospective, monocentric study - Ziegler, Renate; Arnold, Hendrik; Bertram, Ralph; Geißdörfer, Walter; Pauschinger, Matthias; Fischlein, Theodor; Pollari, Francesco; Steinmann, Joerg (Infection, 2023)
PurposeThe spectrum of causative organisms in infective endocarditis (IE) has changed significantly in the last decades. Reliable pathogen detection is crucial for appropriate antimicrobial therapy for IE. The aim of the study was to evaluate the diagnostic value of microbiological methods for detecting the causative microorganism of IE and to analyze the spectrum of pathogens.MethodsA total of 224 cases (211 unique patients, some with multiple surgeries) were included into this retrospective study. Patients were diagnosed with IE according to the modified Duke criteria from January 2016 to July 2021 and underwent heart valve surgery in a tertiary hospital. Pathogen detection was performed by blood culture, microbiological culture and 16S rDNA PCR of explanted heart valve material.ResultsA causative pathogen of IE was detected in 95.5% (n = 214) of cases. Blood cultures were positive in 83.3%, while a pathogen in the examined heart valve samples was identified in 32.6% by culture and in 88.2% by 16S rDNA PCR. A microorganism was identified by 16S rDNA PCR in 61.1% of blood culture negative cases but only in 19.4% by heart valve culture. The most common pathogens were Staphylococcus aureus (27%), viridans group streptococci (20%), enterococci (19%) and coagulase-negative staphylococci (CoNS 8%). Cutibacterium acnes (7%) was detected in prosthetic valve IE cases only.ConclusionBlood culture as a comparatively non-invasive and straightforward technique remains an important and reliable method for initial detection of the causative organism in IE. Diagnostic stewardship programs should broadly emphasize proper collection of blood cultures, particularly sampling prior to any antibiotic treatment. Additionally, molecular testing using 16S rDNA tissue PCR can be used with culture techniques to increase the diagnostic yield, especially in the case of a negative blood culture.
CRIS-Team WoS Importer:2023-04-28